“If I had stayed back home, I would not be alive any more…” – Exploring end-of-life preferences in patients with migration background - Paal, Piret (PLoS One, 2017)
BACKGROUND: In patients with life-limiting conditions and a history of migration, a higher risk of not dying at home and limited access to palliative care services has been reported. AIM: To explore the views and end-of-life preferences of patients with a migration history in Germany and to identify migration specific themes. DESIGN: Two-armed study using Kaufmann’s ‘understanding interview’ (‘focused interview’) method and grounded theory approach. Thematic content analysis was applied using MaxQDA 12 software. SETTING/PARTICIPANTS: Migrant and non-migrant adult patients with far advanced, life-limiting disease receiving palliative care in different specialist level settings (specialist home palliative care, palliative care inpatient unit, inpatient hospice). RESULTS: The 37 interviewees (19 native Germans and 18 patients from Europe and the U.S., Israel, Turkey, and Indonesia) expressed eleven themes covering health care- and patient-related issues, of which four emerged to be specific for migrants: worse survival in home country; the perception of an altered identity and ‘not belonging’; language skills as prerequisite to survive; and longing for ‘home’ while being attached to Germany. From these categories, three overarching themes were derived: (1) a limited understanding of the concept of ‘palliative care’; (2) the suppression of end of life discussions for its association with suffering and loss of autonomy; and (3) the significance of complex individual migration histories. CONCLUSIONS: Based on these findings, the concept of a ‘double home’ experience is proposed. Barriers to access to palliative care should be minimized for all patients while cultural stereotyping has to be avoided.